Effect of Dietary with Different Energy and Protein Levels on Laying Quails Performance - Didik Nur Edi; Faizal Andri (Indonesian Center for Animal Research and Development (ICARD), 2023)
The performance of quail is a function of several production factors, one of which is feed. However, the optimum metabolizable energy and crude protein for the performance of laying quails currently needs to be revised. This study aimed to evaluate the effects of feeding diets with different metabolizable energy and crude protein levels on the performances of laying quails. Five hundred forty (540) laying quails aged eight weeks were randomly allocated into nine dietary treatments. Each treatment consisted of four replicates with 15 laying quails per replicate. Dietary treatments comprised three metabolizable energy levels (2,700, 2,800, and 2,900 kcal/kg) and three crude protein levels (17, 19, and 21%) in a factorial research methodology arrangement. After one week of the adaptation period, the feeding trial was conducted for five weeks (9-13 weeks old). Interaction between metabolizable energy and crude protein levels was recorded on feed intake (P 0.05). Feed intake was reduced along with the increase in the metabolizable energy when crude protein levels were 17 and 19%. However, the feed intake tended to be improved when high metabolizable energy was combined with high crude protein contents (2,900 kcal/kg and 21%, respectively). No interaction was recorded on the other variables (egg production, egg weight, egg mass, and feed conversion ratio) (P 0.05). Feeding diets with different metabolizable energy levels had a significant effect on feed conversion ratio (P 0.05) but without any significant impact on egg production, egg weight, and egg mass of laying quails (P 0.05). Crude protein as a single factor significantly affects egg production, weight, mass, and feed conversion ratio of laying quails (P 0.05). Linear regression analysis indicated that metabolizable energy intake linearly improved egg production, weight, mass, and feed conversion ratio. Moreover, crude protein intake linearly improved egg production, weight, mass, and feed conversion ratio. Therefore, feeding diets containing 2900 kcal/kg metabolizable energy and 21% crude protein are required to provide optimum performance of laying quails.